Comparative outcomes of combined thermal ablation and liver resection versus liver resection alone for multiple colorectal liver metastases: a systematic review and meta-analysis - Meng, Zesong; Li, Baokun; Zhou, Chaoxi; Cao, Longfei; Zhang, Jianfeng; Feng, Jun; Wang, Guiying (Frontiers in Oncology, 2025)
BackgroundThe treatment of colorectal liver metastases (CRLM) continues to pose a significant clinical challenge, with surgical resection remaining the gold standard. However, the efficacy of combining thermal ablation (TA) with liver resection (LR) compared to LR alone in managing multifocal CRLM remains a topic of debate. This meta-analysis aims to compare the outcomes of combining TA and LR with LR alone in patients with multifocal CRLM.MethodsA comprehensive literature search was conducted across PubMed, EMBASE, Cochrane Library, and Web of Science up to December 2024. Studies that compared the combination of TA and LR with LR alone in patients with CRLM and reported at least 1-, 2-, or 3-year overall survival (OS) and/or disease-free survival (DFS) were included. Data were extracted and analyzed using random-effects or fixed-effects models, depending on the degree of heterogeneity. Sensitivity analysis and assessment of publication bias were performed to ensure the robustness of the findings.ResultsSix retrospective cohort studies involving 3084 patients (1286 in the TA+LR group and 1798 in the LR group) were included. No significant differences were found in 1-, 2-, and 3-year OS between the TA+LR and LR groups. However, the TA+LR group exhibited worse DFS. Subgroup analysis revealed a more pronounced decline in DFS in non-European TA+LR cohorts compared to LR cohorts, potentially reflecting regional differences. Additionally, DFS was significantly lower in the radiofrequency ablation (RFA) subgroup compared to the microwave ablation (MWA) subgroup. Complication rates were comparable between the two groups. Sensitivity analysis confirmed the stability of the results, and no significant publication bias was detected.ConclusionCombining thermal ablation with liver resection is a feasible liver-sparing approach for treating extensive CRLM, applicable through both laparoscopic and open surgical techniques. Combined resection and ablation should be considered as an alternative to resection alone for patients with multiple metastases.Systematic review registrationPROSPERO https://www.crd.york.ac.uk/prospero/, identifier CRD42024629343